Tinjauan Hukum Pidana dan Hukum Pidana Islam Terhadap Pelaku Penembakan 6 Anggota Laskar FPI: Studi Putusan Pengadilan Negeri Nomor 86/Pid.B/2021/PN.JKT.Sel - Izzuddin Khisyam Alyasir Samura; Zulkarnain (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This writing discusses a review of criminal law and Islamic criminal law regarding sanctions for the perpetrators of the shooting of six members of the Islamic Defenders Front (FPI) Laskar based on District Court Decision Number 86/Pid.B/2021/PN.Jkt.Sel. In this decision, the perpetrator was acquitted of murder charges on the grounds that the actions carried out fell into the category of self-defense. This research analyzes the application of the concept of self- defense in Indonesian positive criminal law, as well as its implications for law enforcement and social justice. In addition, this study also explores the principles of Islamic criminal law, including the application of qisas and diat, in the context of actions that are considered forced. The findings show that although positive law provides room for self-defense, these decisions raise questions regarding justice for victims and society. In this way, this journal seeks to contribute to the understanding of the interaction between criminal law and Islamic criminal law, as well as its impact on public perception and trust in the justice system.